Research and promotion of spaces: an urgent task to rethink the narratives of menstruation in La Pampa. (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
This article reflects and problematizes the issue of menstruation in the town of Santa Rosa, La Pampa in relation to a series of testimonies on menstruation, in the framework of a menstrual activism by the writer, promoting and dedicating to communication and integral menstrual health. In addition, emerges as an edge of the thesis “Feminist activism in social networks: the case of EcoFeminita and its campaign “MenstruAcción”, research in progress that is being carried out in 2022. From a main introduction, the arguments of the topic will be detailed as well asthe importance of investigating it from the communication. In a second part the results obtained by the data collection will be presented, and ultimately this information will be systematized; to conclude the section with a final reflection.
Keywords: mestruation; pampean experiences; public politics; investigation; communication; social senses